UPAYA GURU DALAM MEMBANTU SISWA MENGINGAT TOKOH-TOKOH PADA PEMBELAJARAN SIROH NABAWIYAH DI KELAS V SDI AL-I’TISHOOM KARAWANG - Afifah Octaviani; Dwi Basuki, Danang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the efforts of teachers in helping students remember figures in the fifth-grade SD Sirah Nabawiyah learning, as well as to identify the forms and factors of difficulty that affect students' ability to memorize figures in Islamic history. This study uses a qualitative approach with a case study research type. The research subjects consist of Sirah teachers and fifth-grade SD students. Data collection techniques were carried out through interviews and documentation. The results of the study show that students still have difficulty remembering the names of figures, distinguishing the roles of the figures, and connecting figures with events. These difficulties are influenced by the large amount of material that must be memorized, limited study time, lack of repetition of the material, and the use of learning methods that are still limited. To overcome these difficulties, the teacher combines the lecture method with storytelling, conducts activities to review previous material, and holds a question-and-answer session at the end of the lesson. This strategy is considered quite effective because students find it easier to understand the material when the teacher explains it directly. This study shows that the teacher’s role is very important in creating engaging learning and helping students understand the figures in the study of Sirah Nabawiyah.